Introducing Foreign Models for Development Japanese Experience and Cooperation in the Age of New Technology - Ohno, Izumi; Jin, Kimiaki; Amatsu, Kuniaki; Mori, Junichi; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2024)
This open access book studies how foreign models of economic development can be effectively learned by and applied to today$1 (Bs latecomer countries. Policy capacity and societal learning are increasingly stressed as pre-conditions for successful catch-up. However, how such learning should be initiated by individual societies with different features needs to be explained. The book answers this pragmatic question from the perspective of Japan$1 (Bs past experience and its extensive development cooperation in Asia, Africa, and Latin America. Since the late nineteenth century, Japan has developed a unique philosophy and method for adopting advanced technologies and systems from the West; the same philosophy and method govern its current cooperation with the developing world. The key concepts are local learning and translative adaptation. Local learning says that development requires the learner to adopt a proactive mindset and the goal of graduating from receiving aid. Meanwhile, translative adaptation requires foreign models be modified to fit local realities given the different structures of the home and foreign society. The development process must be wholly owned by the domestic society in rejection of copy-and-paste acceptance. These ideas not only informed Japan but are key to successful development for all. The book also asks how this learning method should$1 (Bor should not$1 (Bbe revised in the age of SDGs and digitalization. Following the overview section that lays out the general principles, the book offers many real cases from Japan and other countries. The concrete actions outlined in these cases, with close attention to individual growth (3z(Bingredients(3y (Bas opposed to general theories, are crucial to successful policy making. The book contains materials that are highly useful for national leaders and practitioners within developing countries as well as students of development studies. .s
Part I. Translative Adaptation in the Industrialization Process -- 1. Introducing Foreign Models for Development: A Perspective from Translative Adaptation -- 2. Industrial Policies for Learning, Innovation, and Transformation: Insights from Japan and Selected Countries -- Part II. Case Studies from Japan, Asia, Latin America, and Africa -- 3. Japan$1 (Bs State Learning in the Meiji Period from the Vision Perspective -- 4. National Movements for Quality and Productivity Improvement with Local Adaptation: The Experience of Japan and Singapore -- 5. Bilateral Policy Dialogue: Japanese Cooperation for Enhancing Industrial Policy Capacity -- 6. Industry Engagement in TVET and the Japanese Cooperation in Vietnam: The Case of Hanoi University of Industry -- 7. Promoting Kaizen in Africa: 10-Years of Experience of Japanese Cooperation in Tunisia and Ethiopia -- 8. Thailand$1 (Bs Experience of Learning Industrial Technologies and Monodzukuri Education with Localization -- Part III. Translative Adaptationin a Changing World -- 9. Kaizen and Non-cognitive Skills Development in Africa in the Age of Digitalization -- 10. New Industrial Landscape: Implications for Industrial Policy and Japanese Industrial Development Cooperation. .s
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Development economics; Economic development; Globalization; Japan -- History; Development Economics; Development Studies; Economic Growth; Globalization; History of Japan